2010
DOI: 10.1111/j.1468-5957.2010.02198.x
|View full text |Cite
|
Sign up to set email alerts
|

Method‐Shifting in Aggressive Earnings Reporting: The Case of the US Software Industry's Response to New US Regulation

Abstract: Under rationality, firms should shift to alternative earnings management methods to achieve their earnings management goals whenever the alternatives provide greater benefit. New accounting regulation can alter the net benefit derivable from existing earnings management methods and thus may provide the impetus for method-shifting. This study investigates whether firms circumvent regulatory-imposed restrictions on their use of specific methods for accelerating earnings by shifting to alternative methods. Specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Our paper adds to the literature regarding both blockholders and the board of directors' role in providing corporate governance, suggesting that director blockholders are helpful in preventing agency problems in a firm. Previous studies have shown that outside blockholders cannot prevent earnings management and may increase the number of abnormal accruals reported by a firm (Guthrie & Sokolowsky 2010;Zhong et al, 2007). This study shows that, unlike outside blockholders, director blockholders can limit earnings management.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Our paper adds to the literature regarding both blockholders and the board of directors' role in providing corporate governance, suggesting that director blockholders are helpful in preventing agency problems in a firm. Previous studies have shown that outside blockholders cannot prevent earnings management and may increase the number of abnormal accruals reported by a firm (Guthrie & Sokolowsky 2010;Zhong et al, 2007). This study shows that, unlike outside blockholders, director blockholders can limit earnings management.…”
Section: Introductionmentioning
confidence: 52%
“…While one would expect that outside blockholders could limit these accruals due to their role as a corporate governance mechanism, research has shown that outside blockholders typically have little to no impact on lowering abnormal accruals. Zhong et al (2007) assert that firms with declining financial performance tend to manage earnings upward, and pressure to perform for outside blockholders tends to increase this earnings management. Guthrie and Sokolowsky (2010) support this finding by showing that firms with outside blockholders tend to increase abnormal accruals during an SEO more than firms without large outside blockholders.…”
Section: Impact Of Blockholders On Abnormal Accrualsmentioning
confidence: 99%
“…In confirmation of this, in a following study, Stubben (2010) finds that revenue accrual models are more likely than aggregate accrual models to detect a combination of revenue and expense manipulation within a sample of firms subject to SEC enforcement actions. On the other hand, Zhong et al (2010) show that US software firms' method shift from revenue accrual management to expense accrual management in response to the issuance in 1997 of a new reporting standard (SOP 97-2) that places restrictions on the recognition of software revenue. Hence, following previous research (Caylor, 2010;Stubben, 2010;Zhong et al, 2010;Capalbo et al, 2014), this study measures accrual management by estimating discretionary revenue accruals (DREVAC), discretionary expense accruals (DEXPAC) as well as discretionary aggregate accruals (DACC).…”
Section: Discretionary Accruals Proxies and Hypotheses On Accrual Management Within Lmfsmentioning
confidence: 99%
“…On the other hand, Zhong et al (2010) show that US software firms' method shift from revenue accrual management to expense accrual management in response to the issuance in 1997 of a new reporting standard (SOP 97-2) that places restrictions on the recognition of software revenue. Hence, following previous research (Caylor, 2010;Stubben, 2010;Zhong et al, 2010;Capalbo et al, 2014), this study measures accrual management by estimating discretionary revenue accruals (DREVAC), discretionary expense accruals (DEXPAC) as well as discretionary aggregate accruals (DACC). In essence, the authors consider that LMFs may resort to a combination of revenue and expense manipulation, for example, through fictitious transactions, in order to achieve their illicit purposes.…”
Section: Discretionary Accruals Proxies and Hypotheses On Accrual Management Within Lmfsmentioning
confidence: 99%
See 1 more Smart Citation